A rare case of Kunze-Riehm syndrome in a neonate - S., Venugopal; Devadas, Sahana; M., Yashwant (International Journal of Contemporary Pediatrics, 2020)
The Kunze-Riehm syndrome also called as Michelin tire baby syndrome (MTBS), is a rare genodermatosis, characterized by multiple symmetric circumferential folding of excess skin with the various phenotypic abnormality. The diagnosis is made on the basis of the characteristic clinical features in the literature there are approximately 31 cases reported and to the best of our knowledge, this would be the sixth case published from India. Herein authors report a rare case of Kunze- Riehm syndrome in a neonate.